2012
DOI: 10.1038/jhg.2012.92
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies GYS2 as a novel genetic factor for polycystic ovary syndrome through obesity-related condition

Abstract: To investigate the role of genetic predisposition in the pathogenesis of polycystic ovary syndrome (PCOS) in relation to obesity, we performed a genome-wide association study of PCOS in Koreans (n ¼ 1741). PCOS is a heterogeneous endocrinal disorder of uncertain etiology. Obesity is one of the well-known risk factors for PCOS. Genome-wide association study. Women with or without PCOS. A total of 1881 samples were genotyped using Illumina HumanOmni1 Quad v1 and processed by R packages. The PCOS patients were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 42 publications
0
24
0
4
Order By: Relevance
“…A GWAS study conducted by a Korean group failed to confirm these results and found that only the glycogen synthase 2 (GYS2) gene could be linked to PCOS and its metabolic complications (Hwang et al 2012). Another GWAS study conducted in the USA that analysed genes that code for proteins associated with metabolic and cardiovascular abnormalities also did not demonstrate a hereditary component of PCOS .…”
Section: Genetic Factors Associated With Pcosmentioning
confidence: 87%
See 2 more Smart Citations
“…A GWAS study conducted by a Korean group failed to confirm these results and found that only the glycogen synthase 2 (GYS2) gene could be linked to PCOS and its metabolic complications (Hwang et al 2012). Another GWAS study conducted in the USA that analysed genes that code for proteins associated with metabolic and cardiovascular abnormalities also did not demonstrate a hereditary component of PCOS .…”
Section: Genetic Factors Associated With Pcosmentioning
confidence: 87%
“…Because there are three supported definitions of PCOS (Zawadski & Dunaif 1992, Rotterdam ESHRE/ASRM-Sponsored PCOS Consensus Workshop Group 2004, Azziz et al 2006), comparing the results reported in different publications is somewhat difficult. Whereas some authors use a PCOS diagnosis based on criteria listed by the National Institutes of Health (NIH) (Goodarzi et al 2012, Welt et al 2012, Hwang et al 2012, Mutharasan et al 2013, others use the criteria proposed by the American Society of Human Reproduction/European Society of Human Reproduction and Embryology (Chen et al 2011, Shi et al 2012, Hwang et al 2012, Louwers et al 2013, which thereby intensifies discrepancies in the published work on the genetic analysis of PCOS. Some authors have not even attempted to standardise the diagnosis of PCOS (Davies et al 2012, Hizli et al 2012, and they include in their studies women with polycystic ovaries on ultrasonography only, a finding that alone does not increase the risk for PCOS-associated conditions (Cresswell et al 1997), or they collect retrospective data from medical records that antedate the publication of the first consensus on PCOS by the NIH (Mumm et al 2013).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Epidemiológiai adatok alapján egyértelműen felvetődik a PCOS kialakulásában a genetikai faktorok szerepe [8][9][10][11][12][13][14][15][16]. Kutatások alapján látható, hogy monozigóta ikrekben a PCOS előfordulása kétszer gyakoribb, mint dizigótákban.…”
Section: Genetikai Faktorokunclassified
“…to be associated with obesity, elevated testosterone levels, and the metabolic disturbance in PCOS patients [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%